FACTORS OF KINDERGARTEN PRINCIPALS’ LEADERSHIP AFFECTING ADMINISTRATION EFFECTIVENESS OF KINDERGARTEN IN CHAOYANG CITY IN LIAONING PROVINCE - Guanfu, Wang; Muangman, Pornthep; Tipanark, Peerapong (วารสารวิจัยธรรมศึกษา, 2025)
The objectives of this research were: (1) To study the factors of kindergarten principals’ leadership and the components of administration effectiveness of kindergarten in Chaoyang City in Liaoning Province. (2) To examine factors of kindergarten principals’ leadership affecting administration effectiveness in Chaoyang City in Liaoning Province. (3) To propose the guidelines for improving principals’ leadership of kindergarten in Chaoyang City in Liaoning Province. This research was a mixed method research, including quantitative research and qualitative research. The population consisted of 2924 kindergarten principals’ and kindergarten teachers from 84 kindergartens in Chaoyang City in Liaoning Province. The sample size was determined by G* Power program obtained through stratified random sampling technique. There were 257 administrators and teachers in total. The instrument used for collecting data was a five-point rating scale questionnaire. Descriptive statistics and the Exploratory Factor Analysis, Confirmatory Factor Analysis and Structural Equation Model were used to perform data analysis using statistical software. The research findings revealed that; 1) There were 5 factors of kindergarten principals’ leadership affecting administration effectiveness of kindergarten in Chaoyang City in Liaoning Province. 1. Optimize the internal administration 2. Protection and education 3. Curriculum guidance and development 4. Suit the internal and external environment 5. Harmonious and equal employment environment. 2) The factors of kindergarten principals’ leadership affecting administration effectiveness the data analysis results: the factor loading value of optimize the internal administration was 1.00, the factor loading value of Protection and education was 0.86, the factor loading value of Curriculum guidance and development was 0.98, the factor loading value of Suit the internal and external environment was 1.02, the factor loading value of Harmonious and equal employment environment was 1.00, indicated that there was a significant positive impact . 3) There are 33 guidelines for improving principals’ leadership of kindergarten in Chaoyang City in Liaoning Province, including 14 principles for ability to optimize the internal administration, seven principles for the ability of protection and education, five principles for the curriculum guidance and development, and six principles for the ability of transfer ability to suit the internal and external environment, one principle for ability to harmonious and equal employment environment.